A Software Reliability GEP Model Based on Usage Profile - S.J. Sun; J. Xiao (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
In this paper, software reliability measurement is studied from the perspective of usage profile. Reliability parameters on each usage profile are expressed with unascertained rational numbers. Since failure process of each usage profile can be affected by multiple factors such as software attributes and users imports etc., GEP (gene expression programming) is introduced into software reliability modeling, to study comprehensive force among the factors. Finally, a software reliability GEP model based on usage profile is constructed. With the new model, users can confirm software reliability according to its usage, thus enabling software reliability to a more objective assessment. The new model is experimented to measure reliability of SYS in Musa data, and proved with a satisfactory performance. DOI: http://dx.doi.org/10.11591/telkomnika.v10i7.1572